UPAYA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN PENYAKIT INFEKSI MENULAR SEKSUAL MASA PANDEMI COVID-19 DI KABUPATEN BATANG - Luth; Meriwijaya; Muhammad Syaqiq (Journal Publicuho, 2022)
With these various problems, the researchers set the research objective, namely to find out efforts to prevent and control the spread of sexually transmitted infections during the Covid-19 pandemic in Batang Regency and what factors influence it. Data collection in this qualitative descriptive study was carried out in three ways, namely observation, interviews and documentation. The results of this study indicate that efforts to prevent and control sexually transmitted infections, especially HIV/AIDS during the Covid-19 pandemic in Batang Regency are realized through several programs and activities, namely outreach programs, Voluntary Counseling and Testing (VCT), Care Support and Treatment (VCT). CST), Anti Retroviral Therapy (ART), Prevention of Mother-To-Child Transmission (PMTCT), Directly Observed Treatment, Shorourse Chemotherapy (DOTS) and Mentoring. The impact of the COVID-19 pandemic on several STI disease prevention and control programs is in the form of reducing service time even to the point of discontinuing services caused by government policies in dealing with the Covid-19 pandemic. In addition, factors that hinder and support efforts to prevent and control STIs during the COVID-19 pandemic lead to the government's policy of imposing restrictions on community activities and utilizing advances in information technology.